Variable Refrigerant Flow (VRF) System for Space Heating: A Case Study of Resort - Bajracharyaa, Tri Ratna; Bhattaraiai, Rabindra Nath; Mishra, Sarika Kumari; Timilsina, Ashesh Babu (Journal of the Institute of Engineering, 2018)
The need of thermal comfort is one of the major topic of energy consumption in building. Alternative means for space heating are required for reducing building energy consumption and also reduce its carbon footprint. Solar thermal systems are matured technology in field of hot water and space heating. Though solar water heater has flourished in Nepal, space heating system is less popular. With an objective to assess the less popularity of such system in Nepal, financial comparison of solar underfloor heating system against commonly used VRF system designed to meet heating requirements of a particular site is done. The selected site is a resort in Nagarkot, Nepal. The selected site has minimum temperature of 3 ºC which is to be maintained at 20 ºC of which the total heating load is 10.527 kW. From the financial analysis, it is seen that though installation cost of solar powered system is more, in long run it turns out to be economic and in this case the system is technically and financially viable. For solar underfloor heating, the levelized cost of energy when subsidized with 3.5 % interest rate is NRs. 13.18 which is slightly more than current rate of electrical energy. The solar powered heating system has very high footprint because of which this type of system is less employed in urban areas and high rise buildings. Journal of the Institute of Engineering, 2018, 14(1): 1-13